2020
DOI: 10.1101/2020.04.27.065144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topologically correct synthetic reconstruction of pathogen social behavior found in deep tissue sites

Abstract: Within deep tissue sites, extracellular bacterial pathogens often replicate in clusters that are surrounded by immune cells. Disease is modulated by interbacterial interactions as well as bacterial-host cell interactions resulting in microbial growth, phagocytic attack and secretion of host antimicrobial factors. To overcome the limited ability to manipulate these infection sites, we established a system for Yersinia pseudotuberculosis (Yptb) growth in microfluidics-driven microdroplets that regenerates microb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…In comparison with TIMER42, hmp reporter signal was significantly enriched at the periphery (Fig 7B). This hmp reporter signal pattern was consistent with our previously published results (22,26,37) but suggested that NO stress was not significantly slowing bacterial growth within host tissues, based on TIMER42 signal accumulation in some, but not all, peripheral cells. Representative images indicate there was substantial overlap between dps and TIMER42 signals, and that hmp and TIMER42 are detecting distinct subsets of bacteria (Fig 7C).…”
Section: Timer42 Signal Correlates With Dps Expression In Vivosupporting
confidence: 92%
See 1 more Smart Citation
“…In comparison with TIMER42, hmp reporter signal was significantly enriched at the periphery (Fig 7B). This hmp reporter signal pattern was consistent with our previously published results (22,26,37) but suggested that NO stress was not significantly slowing bacterial growth within host tissues, based on TIMER42 signal accumulation in some, but not all, peripheral cells. Representative images indicate there was substantial overlap between dps and TIMER42 signals, and that hmp and TIMER42 are detecting distinct subsets of bacteria (Fig 7C).…”
Section: Timer42 Signal Correlates With Dps Expression In Vivosupporting
confidence: 92%
“…Cultures of the TIMER42 Phmp::gfp and TIMER42 Phmp::gfp-ssrA strains were exposed to 2.5mM DETA-NONOate for 4h, and fluorescence microscopy was used to detect fluorescent signals within individual bacterial cells. The 2.5mM dose was chosen for these experiments based on our previous studies, which showed this dose is sufficient to promote hmp reporter expression (22,26,37). Treatment with the NO donor compound resulted in high levels of hmp reporter expression with both strains (Fig 6A), and TIMER42 signal accumulation (Fig 6B).…”
Section: No Stress Is Sufficient To Promote Timer42 Signal Accumulationmentioning
confidence: 99%